Towards a transnational hip-hop feminist liberatory praxis: a view from the Americas. (3rd March 2016) - Saunders, Tanya
Abstract : The author argues that hip-hop feminism has come to a point where it needs to take a transnationalist turn if it is going to realize its potential to be a twenty-first century feminist praxis. The author highlights how people speaking from a U.S. American context inadvertently become a global referent for anti-oppression movements and subjectivities. Unfortunately, by virtue of being in one of the centers of global power, becoming a global referent of anti-oppression has the potential to distort and even render invisible the realities of Black women throughout the Americas. Through taking a transnational approach to hip-hop feminism, U.S. based advocates can increase the possibilities for hip-hop feminism to function as a politic of solidarity and mutual empowerment for Black women and girls throughout the Americas. Data are drawn from participant observation and interviews conducted in Havana, Cuba (1998–2010), and São Paulo, Brazil (2008–2013).